RUANG BANACH SEBAGAI RUANG OPERATOR YANG DIBANGKITKAN OLEH FUNGSI TERUKUR DAN TERBATAS ESSENSIAL - Muslim A; sumanto sumanto (MATEMATIKA, 2010)
In this paper, we construct a new normed Banach space from collection of all Carleman operators from Hilbert spaceinto Lebesgue space , denoted by with respect to the norm for every generated by an essensially bounded measurable function .